Platform journalism: specifics and trends - Hradziushka, Aleksandr A. (Journal of the Belarusian State University. Journalism, 2023)
This article discusses various aspects of the interaction between news media and non-publisher digital platforms. The role of global digital platforms in the context of increasing competition for the attention of the audience is shown. New models of the Belarusian media in the context of the growing influence of digital platforms are revealed. It is concluded that creating relevant and engaging content, steadily attracting subscribers to communities on digital platforms, and obtaining high reach and citations can be critical components of a platform ecosystem strategy.
Keywords: digital journalism; news media; platforms; publishers; algorithms; platformisation of news; engagement